Office hysteroscopic treatment of a vanishing external uterine orifice in a postmenopausal woman with an obstetrical history of 44 abortions - Maurizio Guida; Lucio M.A. Cipullo; Roberto Iovieno; Anna Rita Palumbo; Giovanni Pontrelli; Gloria Calagna; Attilio Di Spiezio Sardo (Gynecology and Minimally Invasive Therapy, 2015)
Cervical stenosis, defined as cervical scarring of variable degree, represents a significant anatomical impediment to hysteroscopic procedures. Acquired cervical stenoses are more common than congenital forms and they are mainly associated with aging, estrogen–progesteron drugs, cervical trauma or carcinoma. The overcoming of cervical stenosis at office hysteroscopy is challenging and it often fails requiring the scheduling of the patient for an in-patient treatment under general anesthesia. We report the office hysteroscopy treatment of a vanishing external uterine orifice in a postmenopausal woman with an ultrasonographic report of a heterogeneous and thick endometrium suggestive of endometrial pathology, focusing on the main surgical steps to perform an adequate management.